Fórmulas para a vida: o papel da Química na formação de jovens protagonistas - Domingues, Douglas Marques (2025)
Chemistry is a science that studies various topics related to the environment, such as acid rain and the greenhouse effect, issues of utmost importance because they directly influence the nuances of life on the planet. This discipline also addresses the production of medicines, where ethical considerations are essential for the safety and well-being of patients who will consume these products. However, Chemistry education is often seen as a major obstacle by students and society due to its abstract concepts, lack of personal connection to the subject, and the unappealing teaching strategies used by educators. Chemistry, like Biology and Physics, which are part of the trio of natural science subjects, often contributes to students' aversion to studying these subjects. This occurs because these combined factors can lead students to perceive these disciplines as complex challenges, fostering resistance to learning and hindering content assimilation. In the state public schools of São Paulo, there has been an increase in the number of schools accredited in the Full-Time Education Program (PEI), which aims to improve the quality of education in state schools and strengthen youth protagonism, promoting the active participation and engagement of young people in decisions and actions that affect their lives and communities. Considering the students' aversion to natural science subjects and the increase in the number of PEI schools, this research aims to investigate whether and how Chemistry education can contribute to the formation of young protagonists in the context of a PEI school. Specific objectives of this study include: 1) identifying which topics covered in Chemistry classes within the PEI most engage students and understanding why; 2) exploring the teaching strategies used by Chemistry, Science, and Experimental Practices teachers in the PEI; and 3) analyzing how the PEI contributes to Chemistry learning and the development of student protagonism. Data production will involve semi-structured interviews with seven former students, a Chemistry teacher, an Experimental Practices teacher from the high school level, and a Science teacher from the elementary school level. The selection of participants is justified by the diversity of perspectives they offer: the former students will provide insights into their past experiences with Chemistry education and how it affected their development, while the Chemistry teacher and the Experimental Practices teacher will offer a detailed view of the pedagogical practices and their perceptions of their effectiveness. The inclusion of the elementary school Science teacher is crucial to understanding the role of the foundational phase in sparking interest in scientific content and its influence on the transition to high school. These multiple perspectives will help create a comprehensive understanding of the impact of Chemistry education on the formation of young protagonists in the context of the PEI